2020
DOI: 10.1021/acsami.0c15288
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel-Based Hybrid Materials as Antifouling and Fouling-Release Coatings for Marine Applications

Abstract: Hybrid materials (HMs) offer unique properties as they combine inorganic and organic components into a single material. Here we developed HM coatings for marine antifouling applications using sol-gel chemistry and naturally occurring polysaccharides. The coatings were characterized by spectroscopic ellipsometry, contact angle goniometry, AFM, ATR-FTIR, and their stability was tested in saline media. Marine antifouling and fouling-release properties were tested in laboratory assays against the settlement of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 75 publications
(192 reference statements)
0
33
0
Order By: Relevance
“…Different morphologies would complicate the analysis as the surface topography is known to influence the attachment of marine fouling organisms. In terms of elasticity, HEMA was found to be the most rigid and hard coating with a Young’s modulus of 765 MPa, while all other glycol derivatives formed soft and elastic polymer films, expressed in moduli of 2–4 MPa. Softer polymers with a high elasticity are usually considered to be advantageous for fouling-release applications as it supports the removal process of adhered organisms, although recent studies on sol–gel hybrid materials and cross-linked zwitterions demonstrated that higher rigidity caused by high cross-link density can be beneficial for marine applications. …”
Section: Discussionmentioning
confidence: 99%
“…Different morphologies would complicate the analysis as the surface topography is known to influence the attachment of marine fouling organisms. In terms of elasticity, HEMA was found to be the most rigid and hard coating with a Young’s modulus of 765 MPa, while all other glycol derivatives formed soft and elastic polymer films, expressed in moduli of 2–4 MPa. Softer polymers with a high elasticity are usually considered to be advantageous for fouling-release applications as it supports the removal process of adhered organisms, although recent studies on sol–gel hybrid materials and cross-linked zwitterions demonstrated that higher rigidity caused by high cross-link density can be beneficial for marine applications. …”
Section: Discussionmentioning
confidence: 99%
“…Physico-chemical surface properties that deter or exclude fouling settlement are also widely studied. Examples include chemical modification of surface wettability (Li and Guo, 2019), photocatalytic surface chemistry (Zhang et al, 2019;Szeto et al, 2020), oil-or air-trapping polymers (Arnott et al, 2014;Ware et al, 2018), and sol-gels (Richards et al, 2019;Wanka et al, 2020). Many foul-release, surface topography, and physico-chemical approaches show promise, presenting potential avenues for truly environmentally benign and longlasting antifouling protection but product commercialization is low compared to research outputs (Sullivan and O'Callaghan, 2020).…”
Section: Novel Coatings and Surface Materialsmentioning
confidence: 99%
“…Currently, a variety of novel marine antifouling coatings are being developed, including low-surface-energy coatings [10][11][12], antifoulant grafted coatings [13,14], amphiphilic coatings [15,16], main chain degradable coatings [17,18], the resistance of protein adsorption coatings [19,20], biomimetic surface microstructure coatings [21,22], nanocomposite coatings [23,24], hydrogel coatings [25][26][27], and other dynamic surface coatings, etc. However, as a typical representative of self-polishing technology, the widely used tin-free self-polishing coating remains the primary antifouling approach with outstanding antifouling efficacy, a longer-term validity period, and more cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%